Metabolic barriers in non-small cell lung cancer with LKB1 and/or KEAP1 mutations for immunotherapeutic strategies - Tanaka, Ichidai; Koyama, Junji; Itoigawa, Hideyuki; Hayai, Shunsaku; Morise, Masahiro (Frontiers in Oncology, 2023)
Currently, immune checkpoint inhibitors (ICIs) are widely considered the standard initial treatment for advanced non-small cell lung cancer (NSCLC) when there are no targetable driver oncogenic alternations. NSCLC tumors that have two alterations in tumor suppressor genes, such as liver kinase B1 (LKB1) and/or Kelch-like ECHassociated protein 1 (KEAP1), have been found to exhibit reduced responsiveness to these therapeutic strategies, as revealed by multiomics analyses identifying immunosuppressed phenotypes. Recent advancements in various biological approaches have gradually unveiled the molecular mechanisms underlying intrinsic reprogrammed metabolism in tumor cells, which contribute to the evasion of immune responses by the tumor. Notably, metabolic alterations in glycolysis and glutaminolysis have a significant impact on tumor aggressiveness and the remodeling of the tumor microenvironment. Since glucose and glutamine are essential for the proliferation and activation of effector T cells, heightened consumption of these nutrients by tumor cells results in immunosuppression and resistance to ICI therapies. This review provides a comprehensive summary of the clinical efficacies of current therapeutic strategies against NSCLC harboring LKB1 and/or KEAP1 mutations, along with the metabolic alterations in glycolysis and glutaminolysis observed in these cancer cells. Furthermore, ongoing trials targeting these metabolic alterations are 3 discussed as potential approaches to overcome the extremely poor prognosis associated with this type of cancer.